Kontribusi Kualitas Pelayanan Karyawan Front Office kepada Kepuasan Tamu Menginap di Hotel HW Padang - Hasonagon, Rotua Ghani; Youmil, Youmil; Waryono3, Waryono (Journal of Home Economics and Tourism, 2016)
This study aims to explore the contribution of employee service quality Front Office to the satisfaction of the guests staying at the Hotel HW Padang . This research is a quantitative (associative causal). The population in this study is the number of guests staying during the 10 months from January to October 2015 the number of 11,080 people. The number of samples in this study was of 100 people were taken using the formula Riduwan. The sampling technique is non-probability sampling, (incidental sampling). Collecting data using a questionnaire based on the Likert scale that has been tested for validity and reliability. Results of correlation found sig 0.969 > 0.05, then the variable quality of service can not identifies variables guest satisfaction significantly, with R Square of 0.002. This means that Quality Service Customer Satisfaction affects only 0.2% and 99.8 % influenced by factors.Keywords: Quality, Service, Employee, Satisfaction, and Guests.